2008
DOI: 10.3181/0707-rm-207
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Efficacy of Kampo Formulas in a Model of Non Alcoholic Fatty Liver

Abstract: Data on the efficacy of herbal compounds are often burdened by the lack of appropriate controls or a limited statistical power. Treatments to prevent the progression of non alcoholic fatty liver disease (NAFLD) to steatohepatitis (NASH) remain unsatisfactory. A total of 56 rabbits were arrayed into 7 groups fed with standard rabbit chow (SRC), SRC with 1% cholesterol, or each of the five experimental treatments (Kampo formulas 1% keishibukuryogan [KBG], 1% orengedokuto [OGT], and 1% shosaikoto [SST]; vitamin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…TJ-48 was confirmed to possess anti-oxidative, anti-inflammatory, and anti-tumor effects in the liver in a previous animal experiment [22]. There have been only 1 basic study [12] and 1 retrospective clinical study [13] on the effects of JHMs on NAFLD, and TJ-25 showed positive effects in both those studies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…TJ-48 was confirmed to possess anti-oxidative, anti-inflammatory, and anti-tumor effects in the liver in a previous animal experiment [22]. There have been only 1 basic study [12] and 1 retrospective clinical study [13] on the effects of JHMs on NAFLD, and TJ-25 showed positive effects in both those studies.…”
Section: Discussionmentioning
confidence: 84%
“…There has been only 1 report on the effects of JHMs on animal models of NAFLD in which a high-cholesterol diet-fed rabbit model was studied [12]. Although TJ-25 improved lipid profiles and oxidative stress, no JHMs examined significantly improved the plasma AST or ALT levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with an experimental model demonstrated that extracts of Scutellaria baicalensis significantly decreased the plasma total cholesterol and triglyceride levels of rats fed a high-fat diet [20] . Scutellaria baicalensis also reduces plasma triglyceride levels in humans [21] , inhibits the progression of atherosclerosis in rabbits with diet-induced hypercholesterolemia [22] , and improves lipid profiles in a dietary model of NAFLD [23] . However, the molecular basis of pharmacological mechanisms of these hypolipidemic effects is not known.…”
Section: Introductionmentioning
confidence: 99%
“…(RO)) administered to HFD-fed rodents for a period of 15 weeks resulted in an increase in level of adiponectin, an increase in level of circulating endothelial progenitor cells, the upregulation of PPAR- γ , and elevated GSH level in hepatic tissue [63]. Fujimoto et al found that oral administration of Kampo formula keishibukuryogan (KBG) (components: cortex of Cinnamomum cassia J. Presl, radix of Paeonia lactiflora Pall., semen of Prunus persica Batsch, Poria cocos Wolf., and cortex of Paeonia suffruticosa Andrews) for twelve weeks resulted in significant reductions in hepatic TG, fibrosis, and oxidative stress in a rabbit model of NASH [64]. In addition, Zhang et al showed that SNN alleviated hepatosteatosis and improved lipid profiles in Wistar rats that had been exposed to a high caloric diet [65].…”
Section: Recent Studies Of Tcm For Treatment Of Nafldmentioning
confidence: 99%